Effects of nano-sized sodium hexametaphosphate on the viability, metabolism, matrix composition, and structure of dual-species biofilms of Streptococcus mutans and Candida albicans. Issue 4 (21st April 2022) - Sampaio, Caio; Botazzo Delbem, Alberto Carlos; Hosida, Thayse Yumi; de Morais, Leonardo Antônio; Fernandes, Ana Vitória Pereira; Souza Neto, Francisco Nunes; de Camargo, Emerson Rodrigues; Monteiro, Douglas Roberto; Pessan, Juliano Pelim
Abstract: This study evaluated the effects of micrometric or nano-sized sodium hexametaphosphate (HMPnano), combined or not with fluoride (NaF, 1100 ppm), on dual-species biofilms of Streptococcus mutans and Candida albicans . Biofilms were treated with solutions containing the polyphosphates at 0.5% or 1.0%, with/without fluoride (F), in addition to positive and negative controls. Biofilms were analysed by colony-forming units (CFU) counting, metabolic activity, production of biomass, composition of extracellular matrix, and structure. 1% HMPnano + F led to the lowest S. mutans CFU, while C. albicans CFU counts were not affected by any solution. 1% HMPnano led to the lowest metabolic activity, except for 1% HMPnano + F. All solutions promoted reductions in biofilm biomass compared to controls. Also, 1% HMPnano + F promoted the lowest concentrations of carbohydrates in the biofilm matrix, besides substantially affecting biofilms' structure. In conclusion, HMPnano and F promoted higher antibiofilm effects compared with its micrometric counterpart for most of the parameters assessed.